ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN MOBIL HYUNDAI i20 (Studi Kasus Pada Konsumen Mobil Hyundai i20 di Semarang) - Andini, Prisca; Toto Rahardjo, Susilo (Faculty of Economics and Business Diponegoro University, 2012)
This research was motivated by the intense competition in the Indonesian automotive industry with the emergence of various new brands in the market especially hatchback car segment. This is impacting (affect) on sales of Hyundai i20 that far a drift than its competitors. This study aimed to test the effect (influence) of quality, price, promotion, brand awareness, brand image, brand personality, and popularity of consumers' purchase decision on the Hyundai i20. After performing study of literature review and developing hipotheses, the data was collected by questionnaire method toward 100 persons Hyundai i20 car users in Semarang, which is obtained by using purposive sampling technique. Data was analyzed by using quantitative and qualitative anlyses. We then performed an analysis of data obtained by quantitative and qualitative data. A quantitative analysis consist of validity and reliability tests, the classic assumption test, multiple regression analysis, hypothesis testing via t test and F test, and analysis of coefficient of determination (R2). Qualitative analysis is an interpretation of the data collected in this study, and results of data processing that have been implemented with a description and explanation. The results of this research show that a variable quality, price, promotion, brand awareness, brand image, brand personality, and popularity are positive and significant effect of the consumer buying decision variable.